Vacuum brazing of Al2O3 and 3D printed Ti6Al4V lap-joints using high entropy driven AlZnCuFeSi filler - Sharma, Ashutosh; Ahn, Byungmin (Scientific Reports, 2021)
In this work, we studied the brazing characteristics of Al2O3 and 3D printed Ti–6Al–4V alloys using a novel equiatomic AlZnCuFeSi high entropy alloy filler (HEAF). The HEAF was prepared by mechanical alloying of the constituent powder and spark plasma sintering (SPS) approach. The filler microstructure, wettability and melting point were investigated. The mechanical and joint strength properties were also evaluated. The results showed that the developed AlZnCuFeSi HEAF consists of a dual phase (Cu–Zn, face-centered cubic (FCC)) and Al–Fe–Si rich (base centered cubic, BCC) phases. The phase structure of the (Cu–Al + Ti–Fe–Si)/solid solution promises a robust joint between Al2O3 and Ti–6Al–4V. In addition, the joint interfacial reaction was found to be modulated by the brazing temperature and time because of the altered activity of Ti and Zn. The optimum shear strength reached 84 MPa when the joint was brazed at 1050 °C for 60 s. The results can be promising for the integration of completely different materials using the entropy driven fillers developed in this study.